Terpolymer-chitosan membranes as biomaterial - Bravi Costantino, Maria Leticia (2022)
The present study shows a novel copolymer synthesis, its application in the membrane design and the physicochemical and biological characterization of the biomaterial obtained. Terpolymer starting diisopropyl fumarate (F), vinyl benzoate (V) and 2-hydroxyethyl methacrylate (H) was prepared by thermal radical polymerization. This polymer (FVH) was obtained in several monomer ratios and characterized by spectroscopic and chromatographic methods (FTIR, ¹H-NMR and SEC). The best relationship of F:V:H was 5:4:1, which allows efficient interaction with chitosan through cross-linking with borax to achieve scaffolds for potential biomedical applications. The membranes were obtained by solvent casting and analyzed by scanning electron microscopy (SEM), swelling behavior and mechanical properties. In addition, we studied the possible cytotoxicity and biocompatibility of these materials using a murine macrophage-like cell line (RAW 264.7) and bone marrow mesenchymal progenitor cells (BMPC), respectively, taking into account their intended applications. The results of this study show that the terpolymer obtained and its combination with a natural polymer is a very interesting strategy to obtain a biomaterial with possible applications in regenerative medicine and this could be extended to other structurally related systems.